PENGUATAN KARAKTER KEWIRAUSAHAAN MELALUI PENDIDIKAN KELUARGA - Suyahman Suyahman (Jurnal Pendidikan Ilmu Sosial, 2017)
This study aimed to describe the character strengthening kewirausahaanship through education Wirogunan family in the village, District Kartasura, Sukoharjo.This research is a qualitative case study approach. His research interests are the residents in the village Wirogunan as many as 40 families, while the research object is the kewirausahaanial character. Methods of data collection are interviews, observation and documentation. Data analysis techniques using interactive analysis technique consists of three steps: data reduction, data display and data verification.The results showed that the strengthening of the kewirausahaanial character through family education can be done by providing habituation-conditioning on their children to have the kewirausahaanial character and reduce to a minimum dependence on parents. Moreover, it can be done pul a manner giving the example of kewirausahaanship to get their children educated and kewirausahaanial character internalized so as to have a mental attitude that is not always dependent on parents in performing everyday activities in the family. Another way to do consistent with the order that prevailed in the beginning forced keluarega willingly so it will be a habituation run by itself.In conclusion strengthening the kewirausahaanial character must be built from an early age through family education, so that when teenagers and even into adulthood sehingg have the mental attitude of independence and not always rely on others. In this way it will also awaken creativity and innovative power in the face of many challenges in life together in society.